O empreendedorismo de base tecnológica no complexo público de pesquisa em Minas Gerais: um olhar pelo calidoscópio da Teoria Ator-Rede - Tonelli, Dany Flávio (2011)
This thesis aimed at understanding how and under which circumstances researchers and the Public Institutions of Science and Technology (PIST) in the state of Minas Gerais interact to develop a technology-based entrepreneurship (TBE) that takes place at the Public Complex of Scientific Research (PCSR). Thus, this work sought to describe the actions that lead researchers and the PIST to actively engage (or not all) in the initiatives designed to develop the TBEs. In order to achieve this general goal, the Chapter 2, it was developed a theoretical-epistemological approach called Kaleidoscope of the Actor-Network Theory (ANT), which framed specifically the first of the objectives. The remaining objectives were addressed through a theoretical revision on entrepreneurship in Chapter 3; trough an investigation of the political and economic influences that make up the TBE fundaments in the PIST context in Chapter 5; and trough identification and description using explanatory categories based on data. Similarly, the same tack was used in order to assess a proposed comprehension on how the BTE takes place in the Public Complex of Scientific Research (PCSR) in Chapters 6 and 7. Qualitative data (interviews, documents and notes) was gathered from 11 technology transfer and innovation offices in Minas Gerais State and from 17 researchers from several research areas involved in BTE activities. With this empirical framework, this research core was completed and it was adopted an analytical technique inspired in the Grounded Theory (STRAUS; CORBIN, 2008). Once the central category (the BTE construction at the PIST in the state of Minas Gerais) and the analytical scope (the nonhuman-network and the human-network) were defined, the coding techniques based on data allowed the development of the following categories (i) the pre-stabilization of the object; (ii) materialized objects; (iii) information as (a; an) (in) consistency optical, and (iv) human engagement. In general, the results showed the explanatory relevance of the basic assumption, which argues that the BTE at the PCSR cannot be reduced to initiatives by people with exceptional characteristics, nor it can be constrained by imposed issues pertaining to a material structure, as an outside-in movement. By analyzing the study object through the ANT kaleidoscope, it was possible to realize that the BTE is characterized by the association of many heterogeneous elements, disjunctively dispersed in time and space and by the consequent stabilization of those around objects that are effective in creating conjunction and meaning. Such an understanding also shows the effectiveness of another argument, which is the assumption that the BTE is a set of actions distributed among symmetrical, inextricably linked and simultaneous human and non-human elements.